Severe/Extreme Hypertriglyceridemia and LDL Apheretic Treatment: Review of the Literature, Original Findings. (15th December 2014) - Diakoumakou, Olga; Hatzigeorgiou, Georgios; Gontoras, Nikos; Boutsikou, Maria; Kolovou, Vana; Mavrogeni, Sophie; Giannakopoulou, Vassiliki; Kolovou, Genovefa D.
Abstract : Hypertriglyceridemia (HTG) is a feature of numerous metabolic disorders including dyslipidemias, metabolic syndrome, and diabetes mellitus type 2 and can increase the risk of premature coronary artery disease. HTG may also be due to genetic factors (called primary HTG) and particularly the severe/extreme HTG (SEHTG), which is a usually rare genetic disorder. Even rarer are secondary cases of SEHTG caused by autoimmune disease. This review considers the causes of SEHTG, and their management including treatment with low density lipoprotein apheresis and analyzes the original findings.